(untitled) (Epidemiology, Biostatistics, and Public Health, 2024)
Objectives: To describe the phenomenology of ketamine use; to identify feared/unwanted consequences due to the use of ketamine; to identify any common ketamine consumption rules. Methods: A semi-structured questionnaire was administered to a sample of 48 (31.3% female) substance users living in Italy with recent use of ketamine (last 12 months) and who have never referred to an Addiction Service. Results: From the results aspects emerge related to particular strategies implemented by interviewees to reduce the impact of ketamine consumption on their health, in everyday life and within social relationships: 1) ketamine consumption and purchase were primarily based on friendship networks and trusted relationships; 2) techniques of camouflage were adopted to keep the consumer status secret; 3) artisan controls to verify the quality of the substances were common; 4) general consumption rules were implemented to avoid unwanted consequences due to the use of ketamine. Conclusions: The control of ketamine consumption is a complex practice that includes various aspects related not only to the knowledge of the substance, to the dosing-related harm reduction strategies, to the consumption setting, and to the consumer’s psycho-physical state, but also to the choice of people to buy from and consume with.